2021
DOI: 10.1177/01614681211059018
|View full text |Cite
|
Sign up to set email alerts
|

Moving toward stronger advising practices: How Black males’ experiences at HPWIs advance a more caring and wholeness-promoting framework for graduate advising

Abstract: Background: Graduate education provides students with specialized skills needed to advance science and discovery and prepares future educators and role models for future generations of learners. Given the importance of graduate education, the estimate that more than half of the students who begin it do not complete their degrees is troubling. Existing scholarship suggests that this substantial attrition from graduate school is in part due to inadequate advising. To address this concern, it is important to exam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 59 publications
1
13
0
Order By: Relevance
“…Boikhutso and colleagues (2013) also reported factors that contribute to poor supervisory characteristics. As examples, the authors reported that students faced challenges in their groups when their PIs were not easily accessible for consultation, or were accessible but tended to offer unsupportive feedback, a finding also reported by Burt et al (2021), who described the complicated nature of research group experiences when the PI is also the students' advisor.…”
Section: Influences Of Research Supervision On Studentsmentioning
confidence: 79%
See 1 more Smart Citation
“…Boikhutso and colleagues (2013) also reported factors that contribute to poor supervisory characteristics. As examples, the authors reported that students faced challenges in their groups when their PIs were not easily accessible for consultation, or were accessible but tended to offer unsupportive feedback, a finding also reported by Burt et al (2021), who described the complicated nature of research group experiences when the PI is also the students' advisor.…”
Section: Influences Of Research Supervision On Studentsmentioning
confidence: 79%
“…Small Group Research, 53(6), 855-890. https://doi.org/10.1177/10464964221097699. Burt, B. A., McCallum, C. M., Wallace, J. D., Roberson, J., Bonanno, A., & Boerman, E. (2021).…”
Section: Declaration Of Conflicting Interestsmentioning
confidence: 99%
“…A quality relationship with and ongoing access to a primary or research advisor strongly supports graduate degree persistence (Bégin & Gérard, 2013;Gittings et al, 2018;Main, 2018;NASEM, 2018). Advisors who provide graduate students with consistent and constructive guidance throughout the students' research experience generate a stronger, more successful advising relationship and independence for the student (Blume-Kohout, 2017;Burt et al, 2021;Kerr et al, 2018;Zhao et al, 2007). While the importance and influence of advisor relationships on degree completion are evident, the influence of and changes to advisor relationships have yet to lead to increased degree completion (Burt et al, 2021).…”
Section: Advisor Relationshipsmentioning
confidence: 99%
“…Advisors who provide graduate students with consistent and constructive guidance throughout the students' research experience generate a stronger, more successful advising relationship and independence for the student (Blume-Kohout, 2017;Burt et al, 2021;Kerr et al, 2018;Zhao et al, 2007). While the importance and influence of advisor relationships on degree completion are evident, the influence of and changes to advisor relationships have yet to lead to increased degree completion (Burt et al, 2021). The association between advisor relationship and degree completion intentions has yet to be quantitatively assessed in engineering graduate students.…”
Section: Advisor Relationshipsmentioning
confidence: 99%
“…While rarely addressed directly, there is research that suggests that students’ relationships with faculty can influence how stress and mental health issues are managed. Positive interactions, emotional competency and demonstrations of care and concern from faculty are linked to graduate students’ satisfaction and sense of belonging in graduate school and can translate to their ability to manage their academic programs (Burt et al , 2021; O’Meara et al , 2013; Tenenbaum et al , 2001). Faculty support can enhance students’ confidence (Curtin et al , 2016; Griffin et al , 2020) and mitigate emotional stress.…”
Section: Introductionmentioning
confidence: 99%